Tradisi Tebokan dalam Perspektif Pengembangan Usaha Mikro Kecil Menengah (UMKM) Masyarakat Kaliputu Kota Kudus - Maula, Ni'matul (Mafa Press, 2024)
The tradition of Tebokan in Kaliputu Village, Kudus, is a local cultural heritage that strengthens community identity and plays an important role in economic development through the involvement of Micro, Small and Medium Enterprises (MSMEs). This annual event, which coincides with the celebration of 1 Muharram, combines religious values and local culture with a procession of gunungan jenang that symbolizes prosperity. This research uses a descriptive qualitative approach with data collection techniques in the form of interviews, documentation, and literature studies. The results showed that Tebokan Tradition is not only a cultural ritual, but also serves as a promotional strategy that supports the growth of jenang MSMEs. Government support and synergy between MSME players and the local community have increased the popularity of jenang as a local superior product, while strengthening the village economy. Despite facing obstacles, such as limited budget and community participation, this tradition still has great potential to grow through cross-sector collaboration. Through the preservation of the Tebokan Tradition, Kaliputu Village not only maintains its cultural heritage but also strengthens economic resilience and enriches the social life of the community.